Modulation of Neuronal Survival Factor MEF2 by Kinases in Parkinson’s Disease - Yin, Yue; She, Hua; Li, Wenming; Yang, Qian; Mao, Zixu (Frontiers in Physiology, 2012)
Parkinson’s disease (PD) is the second most common neurodegenerative disorder due to selective death of neurons in the substantia nigra pars compacta (SNpc). The cause of cell death remains largely unknown. Myocyte enhancer factor 2 (MEF2) is a group of transcriptional factors required to regulate neuronal development, synaptic plasticity, as well as survival. Recent studies show that MEF2 functions are regulated in multiple subcellular organelles and suggest that dysregulation of MEF2 plays essential roles in the pathogenesis of PD. Many kinases associated with transcription, translation, protein misfolding, autophagy, and cellular energy homeostasis are involved in the neurodegenerative process. Following the first demonstration that mitogen-activated protein kinase p38 (p38 MAPK) directly phosphorylates and activates MEF2 to promote neuronal survival, several other kinase regulators of MEF2s have been identified. These include protein kinase A (PKA) and extracellular signal regulated kinase 5 (ERK5) as positive MEF2 regulators, and cyclin-dependent kinase 5 (Cdk5) and glycogen synthase kinase 3β (GSK3β) as negative regulators in response to diverse toxic signals relevant to PD. It is clear that MEF2 has emerged as a key point where survival and death signals converge to exert their regulatory effects, and dysregulation of MEF2 function in multiple subcellular organelles may underlie PD pathogenesis. Moreover, several other kinases such as leucine-rich repeat kinase 2 (LRRK2) and PTEN-induced putative kinase 1 (PINK1) are of particular interest due to their potential interaction with MEF2.